Experimental Study of the Effect of Tetraethoxysilane on Mechanical Properties of Silicone Rubber - Polyurethane Blend - Hayder Adnan Abdulhussain; Mohammed Hamzah Daham; Ahmed Fadhil Hamzah (Migration Letters, 2023)
Mixing polymeric materials to obtain a blend is considered very important. To improve mechanical properties, as the extent of compatibility and the type of bonding between the blend components greatly affect the properties of the resulting blend, especially the mechanical properties and physical properties in general. The current research shows that it is important to study how compatibility and chemical and physical bonding affect the mechanical and other properties of the polymeric blend made when thermosetting is used. Herein, silicone rubber (SR) is mixed with polyurethane (PU) with the help of a substance called tetraethoxysilane (TEOS) to improve the compatibility and chemical bonding between the components of the blend. This was done by studying the internal structure of each material separately and the possibility of compatibility between the blend’s components. Besides, mixing (80%) resin of SR with 0.1% (TEOS) and then mixing with (20%) polyurethane and then adding hardeners for each one, respectively, to form an interpenetrating polymer network. The findings show that a mixture (IPN) is physically and chemically bonded, and this indicates an increase in some mechanical properties as the tensile strength increased to 0.5 KPa. Tear strength increased to 12 KPa, which also increased the number of fatigue cycles to (3,100,023 cycles, and a decrease in the swelling ratio was also observed to 3.4 %. The examination of Fourier transforms infrared spectroscopy (FTIR) confirmed the existence of chemical bonds (crosslink) between (SR) and (PU) through (TEOS). Scanning Electron Microscopy (SEM) also confirmed the decrease in micro-gaps, which are the starting point for failure in most mechanical properties.